ANALYSIS OF A THREE PHASE SINGLE STAGE PFC BY USING FLYING CAPACITOR (International Journal of Engineering Management Science, 2022)
Today the wide usage of non linear loads like variable speed drives has made power factor improvement difficult due to the presence of harmonic currents. These harmonics cause overheating, and the amplification of these harmonics cause failure damage of Capacitors and other system components. Thus this paper presents a new integrated AC-DC converter with single stage power factor correction with flying Capacitor. Due to the interleaved structure, the proposed converter operates at lower input ripple current and has improved load efficiency along with peak switch currents and soft switch operation. The convertor has improved efficiency and due to single stage 3 level AC-DC converter it has voltage regulation along with power factor correction. In the paper, the operation of the converter is explained, the steady state characteristics of the new converter are determined and its design is discussed. The feasibility of the new converter is confirmed with experimental results obtained from a prototype converter and its efficiency is compared to that of another multilevel converter